Have CEOs changed? - Decressin, Yann; Kaplan, Steven N.; Sorensen, Morten (Journal of Financial Economics, 2025)
Using more than 4900 personality assessments, we study changes in the characteristics of CEOs and top executives since 2001. The same four factors explain roughly half of the variation in executive characteristics in this larger sample of assessments as in Kaplan and Sorensen (2021). In later years, CEO candidates have shown declining general ability, are increasingly execution-oriented, less interpersonal, less charismatic, and less creative-strategic, and many of these differences persist for hired CEOs. We find no evidence of increasing prevalence or importance of interpersonal and softer skills. Executives assessed for the same company have positively correlated abilities, suggesting that high-ability executives complement each other. Finally, we consider corporate objectives and CEO characteristics.